Elliptical slot circular patch antenna array with dual band behaviour for future 5G mobile communication networks - Khattak, M.I. (2019)
This paper presents a dual band circular microstrip patch antenna with an elliptical slot for future 5G mobile communication networks. The antenna has resonating frequencies of 28 GHz and 45 GHz, with bandwidths of 1.3 GHz and 1 GHz, respectively. Efficiency of the antenna is 85.6 at 28 GHz and 95.3 at 45 GHz. The return loss at 28 GHz is â40 dB, with maximum gain of 7.6 dB while at 45 GHz return loss is â14 dB with maximum gain of 7.21 dB. The antenna is designed on a Rogers RT5880 (lossy) substrate with dielectric constant of 2.2 and loss tangent (tan Î´) of 0.0013. The antenna has a compact size of 6 Ã 6 Ã 0.578 mm 3 . Array configuration is used to achieve 12 dB gain, required for mobile communication. The proposed array has resonance frequencies of 28 GHz, 34 GHz and 45 GHz with maximum gain of 13.5 dB and radiation efficiency of 98.75. Centre series fed technique is used for the excitation of array. SAR value of array antenna obtained at 28 GHz is 1.19 W/kg, at 34 GHz is 1.16 W/kg, and at 45 GHz is 1.2 W/kg. CST Microwave Studio, a 3D simulating tool, is used for the antenna design and calculation of the antenna parameters along with the SAR analysis. Â© 2019, Electromagnetics Academy. All rights reserved.